Selênio e iodo na qualidade de uvas e sucos da cultivar bordô produzidos em regiões subtropicais - Ramos Filho, Fabiano Luis de Sousa (2025)
The production of table grapes and juices from american and european grapes in Minas Gerais State, although still incipient, has gained prominence due to the increase in consumption in Brazil. Winemaking in Brazil has demonstrated great commercial value, but climate change has been affecting grape production worldwide. This is seen in viticulture practiced in subtropical zones. Agronomic biofortification is a strategy that, in addition to aiming to combat hidden hunger, which would be the lack of micronutrients essential to the human body that can be consumed through food, acts as a reinforcement in the ability to combat oxidative stress caused by free radicals, strengthening plant development and thus making plants less sensitive to abiotic stress. Thus, agronomic biofortification with selenium and iodine can contribute to plant development. Thus, this work aimed to evaluate the influence of the application of selenium and iodine, based on agronomic biofortification, on improving vegetative and productive development, in addition to the quality of vine fruits. The work was carried out at the EPAMIG Experimental Field in Caldas, Minas Gerais State, Brazil. Treatments with selenium and iodine were applied, during the flowering period and at veraison on plants of the cultivar ‘Bordo clone 16’ (Bocaina). Pruning weight, production, fruit quality and juices produced were evaluated in two harvest cycles. The analysis showed that the treatments containing lodate + Fisium Se and lodate + Sodium Selenate demonstrated the best performances throughout the two cycles.